2019
DOI: 10.3389/fmicb.2019.02492
|View full text |Cite
|
Sign up to set email alerts
|

Do Organic Substrates Drive Microbial Community Interactions in Arctic Snow?

Abstract: The effect of nutrients on microbial interactions, including competition and collaboration, has mainly been studied in laboratories, but their potential application to complex ecosystems is unknown. Here, we examined the effect of changes in organic acids among other parameters on snow microbial communities in situ over 2 months. We compared snow bacterial communities from a low organic acid content period to that from a higher organic acid period. We hypothesized that an increase in organic acids would shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…We also found that in the late spring samples the abundance of sequencing reads mapping to the components of the fatty acid synthesis-related microbial pathways significantly correlated with organic acid levels. Both of these findings are consistent with a period of microbial community growth, in line with the previous finding of the switch from microbial cooperation to competition [33]. We further observed that the rise in organic acid levels correlated with the appearance of the geraniol degradation pathway and disappearance of the styrene degradation pathway.…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…We also found that in the late spring samples the abundance of sequencing reads mapping to the components of the fatty acid synthesis-related microbial pathways significantly correlated with organic acid levels. Both of these findings are consistent with a period of microbial community growth, in line with the previous finding of the switch from microbial cooperation to competition [33]. We further observed that the rise in organic acid levels correlated with the appearance of the geraniol degradation pathway and disappearance of the styrene degradation pathway.…”
Section: Introductionsupporting
confidence: 92%
“…With the warming in the late spring, the active community made up a larger fraction of the sequenced reads and, thus, manifested in more homogeneity. Previous 16S rRNA-based taxonomic analysis on the same dataset observed a shift in the community from early to late spring [33]. While the early spring samples contained a core community of 59 OTUs, there were only 29 OTUs in the late spring samples, with 42 early spring core OTUs disappearing from the core community of late spring samples [33].…”
Section: Early-to-late-spring Dissimilarity and Metagenome-to-transcrmentioning
confidence: 70%
See 3 more Smart Citations